2019
DOI: 10.3386/w25657
|View full text |Cite
|
Sign up to set email alerts
|

Administrative Data Linking and Statistical Power Problems in Randomized Experiments

Abstract: NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 116 publications
0
2
0
Order By: Relevance
“…Tahamont et al. (2020) show that minimizing the sum of false positive and false negative error rates minimizes the bias introduced by linking errors when linking administrative records to identify the presence of a binary outcome, as we do in this paper. Consequently, including the probabilistic matching tier is preferable to excluding it.…”
Section: Setting and Datamentioning
confidence: 63%
See 1 more Smart Citation
“…Tahamont et al. (2020) show that minimizing the sum of false positive and false negative error rates minimizes the bias introduced by linking errors when linking administrative records to identify the presence of a binary outcome, as we do in this paper. Consequently, including the probabilistic matching tier is preferable to excluding it.…”
Section: Setting and Datamentioning
confidence: 63%
“…As might be expected, the validation procedure revealed that many of the false positives came from the probabilistic matching tier (the exact matching process had a 0.8 percent false positive error rate and 8.0 percent false negative error rate). Tahamont et al (2020) show that minimizing the sum of false positive and false negative error rates minimizes the bias introduced by linking errors when linking administrative records to identify the presence of a binary outcome, as we do in this paper. Consequently, including the probabilistic matching tier is preferable to excluding it.…”
Section: Matching Processmentioning
confidence: 65%